Brief reflections on History of Medicine and the use of 'garum' as medication - Duprat, Paulo (Romanitas - Revista de Estudos Grecolatinos, 2025)
In this contribution, I seek to provide a very brief comparative perspective between ancient and modern medicine, outlining a historical background that I believe is pertinent and didactic for my main theme, which is the use of garum as a medication in ancient medicine and veterinary medicine. In doing so, I present the human practice of care under a more revealing time continuum, attempting to demonstrate that our current level of knowledge about medicine is very recent and that we need to respect the legacy of the ancients.
Keywords: History of Medicine; History of techniques; Ancient Medicine; Ancient Veterinary; Ancient Pharmacology; Garum